PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK SISWA DI SEKOLAH MTs. AL-ISLAMIYAH - Fitriani, Lia; Agil, Muhammad; Hermansyah, Endang (LP2M JAMIAT KHEIR, 2024)
teachers in shaping the morals of class VII students at MTs Al Islamiyah. Using a qualitative approach with narrative descriptive methods, this research analyzes data obtained from observation, interviews and documentation. The research results show that PAI teachers have a very significant role in shaping student morals. Various learning strategies, such as active-collaborative learning and exemplary approaches, have succeeded in improving the quality of students' manners towards teachers and creating conducive classroom conditions. A comprehensive moral training program, which includes daily habituation, mentoring, and periodic evaluations, also has a positive impact on students' cognitive, affective, and psychomotor aspects. Other findings show that supporting factors such as support from the madrasah principal, school committee, and parents are very important. important to the success of the program. However, the influence of social media and limited learning time are challenges that need to be overcome. This research concludes that PAI teachers have a multidimensional role in shaping student morals. Apart from being teachers, PAI teachers also act as mentors, role models, motivators and evaluators. Integration of PAI learning with students' daily lives, as well as collaboration with various related parties, is the key to success in shaping student character.